Adenosine deaminase and interferon-gamma in diagnosis of tubercular pleural effusion - Jethani, Varuna; Sindhwani, Girish; Mehrotra, Vinit; Kotwal, Aarti; Khanduri, Rakhee (International Journal of Research in Medical Sciences, 2016)
Background: Pleural effusion is a common extrapulmonary manifestation of tuberculosis (TB). The conventional culture suffers from lack of sensitivity. Many pleural fluid markers have been evaluated to diagnose tubercular pleural fluid but none has proved to be an ideal. We have studied Adenosine deaminase (ADA), Interferon gamma (IFN) and their combination for diagnosis of tubercular pleural effusion. Methods: All consecutive patients with pleural effusion were subjected to thoracentesis and segregated into transudative and exudative using Light`s criteria. Patients with exudative pleural effusion were enrolled and divided into two groups. Group-I comprised of patients with tubercular etiology, Group-II- non-tubercular etiology. 45 patients were selected for each group. ADA and IFN in pleural fluid of these patients were measured. The sensitivity, specificity and predictive values were calculated. Results: The sensitivity, specificity, positive predictive value, negative predictive value of ADA and IFN were 88.89%, 99.85%, 86.96%, 99.87%; 97.78%, 97.78%, 97.78%, 97.78% respectively. Combination of ADA and IFN didn’t improve the sensitivity or specificity compared to IFN alone. Conclusions: Pleural fluid ADA, IFN were found to be useful in differentiating tubercular from non-tubercular patients. Combination of ADA and IFN doesn’t give additional benefit over IFN alone.